Sustainable Economic Practices in Rural Indonesia: Balancing Tradition and Modernity in Post-Pandemic Era - Ahmad Maulana; Nizar Zakaria; Doni Fitriyanto (Commodities, Journal of Economic and Business, 2025)
This study examines the sustainable economic transformation in rural Indonesia through a case study of Warujayeng Village, East Java, focusing on the integration of traditional practices and modern innovations in the post-pandemic era. The research addresses how rural communities navigate economic resilience by synthesizing local wisdom with technological advancements, challenging conventional modernization paradigms. Employing a qualitative approach with participatory observation, in-depth interviews, and document analysis, the study reveals three key adaptation phases: selective resistance, limited experimentation, and hybrid practice institutionalization. Findings demonstrate that 72% of traditional traders adopted digital platforms while maintaining interpersonal transactions, and polyculture farming systems showed 23% greater resilience than monocultures during crises. The study contributes to development theory by introducing "culturalized innovation" and "digital embeddedness" concepts, highlighting informal institutions as crucial innovation mediators. Practical implications suggest culturally sensitive policy frameworks for rural development, emphasizing asset-based approaches and spiritual-social capital integration.